Quick & easy decorative painting - Jessee, Peggy, 1947- (Cincinnati, Ohio : North Light Books, 2000)
Hundreds of illustrated steps show simple ways to paint favorite flowers, fruits and berries on inexpensive items, such as wooden spoons, candy jars and baskets. Just follow the clear directions and hands-on photos to create beautiful rosebuds, tulips, mums, strawberries, apples, grapes and more. Simply mix and match these subjects to create an infinite variety of designs. You'll even find creative tips for adapting motifs and colors to create your very own, quick-and-easy originals!--Page 4 of cover
Includes index.
Keywords: Painting; Decoration and ornament -- Plant forms